Exploring the Potential of Selenium-Containing Amine (Se-AMA) to Enhance Photosynthesis and Leaf Water Content: New Avenues for Carbonic Anhydrase Modulation in Arabidopsis thaliana - Sara Beltrami; Francesca Alderotti; Antonella Capperucci; Damiano Tanini; Cecilia Brunetti; Francesco Ferrini; Ermes Lo Piccolo; Antonella Gori (Plants)
Global changes and growing demands have led to the development of new molecular approaches to improve crop physiological performances. Carbonic anhydrase (CA) enzymes, ubiquitous across various life kingdoms, stand out for their critical roles in plant photosynthesis and water relations. We hypothesize that the modulators of human CAs could affect plant physiology. Our research demonstrated that foliar treatments with a synthetic selenium-containing CA activator (Se-AMA) influenced the physiological performances of Arabidopsis thaliana. Se-AMA increased net photosynthesis (A + 31.7%) and stomatal conductance (gs + 48.2%) at 100 µM, with the most notable effects after 10 days of treatment. Se-AMA at 300 µM proved to be even more effective, boosting A and gs by 19.9% and 55.3%, respectively, already after 3 days of application. Morning treatment with Se-AMA at 300 µM enhanced photosynthetic performances throughout the day, suggesting that the positive effect of Se-AMA lasted for several hours. Additionally, Se-AMA increased water content in plants by 17.1%, suggesting that Se-AMA treatment may have improved plant water absorption and resource management. This effect might be linked to Se-AMA’s role in modulating specific CA isoforms working with aquaporins. Although preliminary, these findings suggest that Se-AMA could enhance plant physiological performances under the conditions of non-limiting water availability.